Geodetic investigation of Torfajokull Volcano, Iceland - Scheiber, Stephanie Elizabeth (My University, 2009)
The Mid-Atlantic ridge and North Atlantic mantle plume interaction is expressed in south Iceland as two overlapping, subparallel spreading centres; the Western (WVZ) and Eastern Volcanic Zones (EVZ). The South Iceland Seismic Zone (SISZ), a transform fault, connects these systems. Plate motion is partitioned across these zones and is accommodated by repeated lateral dyke injection from central volcanoes into fissure swarms within the volcanic zones. South of the SISZ-EVZ intersection, also the location of Torfajökull volcano, the EVZ is propagating to the southwest into the Eastern Volcanic Flank Zone (EVFZ). The plate spreading south of Torfajökull appears to be partitioned across the Reykjanes Peninsula (RP) in the west and the EVFZ. This study investigates the complex interplay between plate spreading and volcano deformation in the region surrounding Torfajökull volcano using space geodetic and modelling techniques. We present a new horizontal velocity field based on episodic GPS measurements collected between 2000 and 2006 in the southern part of the EVZ. This velocity field is compared to a GPS-derived velocity field from 1994-2003 (LaFemina et al. 2005) and elastic half-space plate spreading models. In a stable Eurasian reference frame the horizontal signal is dominated by plate spreading through the caldera, in agreement with known Holocene fissuring to the northeast along the Veidivötn fissure swarm and southwest of the caldera. It is shown that spreading is occurring across the EVFZ, with maximum strain accumulation during this inter-rifting period along the western edge of the Eldgjá fissure swarm which was last active in 934 A.D. These locations have major implications for the location of future rifting events as it is presumed that significant subsurface magma accumulation occurs along the centre of spreading. Spreading rates for this study show along strike variations, decreasing from 10-20 mm/yr to the north of Torfajökull to 7-8 mm/yr in the south, which is in line with a simple propagating ridge model and previous studies. Locking depths for these dyke models are relatively shallow (<6 km). The horizontal velocity field also indicates the interaction of Hekla volcano situated in the northwest of the study area, as the volcano has been uplifting since its last eruption in 2000, as well as subsidence due to a possible slow cooling magma chamber in the western part of Torfajökull which is supported by InSAR and “dry-tilt” data.